2012
DOI: 10.1242/dev.077412
|View full text |Cite
|
Sign up to set email alerts
|

Mei-P26 regulates the maintenance of ovarian germline stem cells by promoting BMP signaling

Abstract: SUMMARYIn the Drosophila ovary, bone morphogenetic protein (BMP) ligands maintain germline stem cells (GSCs) in an undifferentiated state. The activation of the BMP pathway within GSCs results in the transcriptional repression of the differentiation factor bag of marbles (bam). The Nanos-Pumilio translational repressor complex and the miRNA pathway also help to promote GSC selfrenewal. How the activities of different transcriptional and translational regulators are coordinated to keep the GSC in an undifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(128 citation statements)
references
References 58 publications
2
120
1
5
Order By: Relevance
“…Mei-p26 is involved in germ cell development in Drosophila (22)(23)(24). Previous reports have shown that translation of mei-P26 mRNA is controlled by Bam, Bgcn, CCR4, Vasa, and Tut (22,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Mei-p26 is involved in germ cell development in Drosophila (22)(23)(24). Previous reports have shown that translation of mei-P26 mRNA is controlled by Bam, Bgcn, CCR4, Vasa, and Tut (22,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several TRIM-NHL proteins (including Drosophila Brat, Mei-P26, and Wech/Dappled; C. elegans NHL-2 and LIN-41; or mammalian TRIM2, TRIM3, TRIM32, and TRIM71) were found associated with RNA-protein complexes (RNPs) (Kanai et al 2004;Duchaine et al 2006;Neumuller et al 2008;Hammell et al 2009;Rybak et al 2009;Schwamborn et al 2009;Chang et al 2012;Li et al 2012Li et al , 2013Loedige et al 2013), and, in some cases, these interactions were shown to be dependent on either the RNA (Hammell et al 2009;Chang et al 2012;Li et al 2012) or the respective NHL domain within the RNP (Neumuller et al 2008;Schwamborn et al 2009;Chang et al 2012;Loedige et al 2013). In addition to Brat, Mei-P26 and TRIM71 were also recently shown to repress translation (Chang et al 2012;Li et al 2012Li et al , 2013Loedige et al 2013), and C. elegans LIN-41 and human TRIM71/ LIN-41 regulate expression of the transcription factors LIN-29 and EGR1, respectively, possibly at the level of translation (Slack et al 2000;Worringer et al 2014). In all cases, repression depends on the NHL domain (Slack et al 2000;Chang et al 2012;Li et al 2012;Loedige et al 2013).…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…In addition to Brat, Mei-P26 and TRIM71 were also recently shown to repress translation (Chang et al 2012;Li et al 2012Li et al , 2013Loedige et al 2013), and C. elegans LIN-41 and human TRIM71/ LIN-41 regulate expression of the transcription factors LIN-29 and EGR1, respectively, possibly at the level of translation (Slack et al 2000;Worringer et al 2014). In all cases, repression depends on the NHL domain (Slack et al 2000;Chang et al 2012;Li et al 2012;Loedige et al 2013). In support of a direct RNA-binding activity, the aforementioned mRNA interactome studies identified TRIM71 and TRIM56 as putative novel RNA-binding proteins (Baltz et al 2012;Castello et al 2012;Kwon et al 2013), and, in case of TRIM71, direct RNA-binding was verified and mapped to the NHL domain (Kwon et al 2013).…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…In contrast, overexpressing a form of Mei-P26 lacking the NHL domain, which mediates specific protein-protein interactions, did not affect dMyc levels ( Figure S2B). Equivalent amounts of fulllength Mei-P26 and the truncated version were found to be expressed with the GAL4/UAS system in the Drosophila ovary (Li et al 2012). Thus, both the ubiquitin ligase activity (Herranz et al 2010) and the NHL domain (this work) of Mei-P26 are required to target dMyc for degradation.…”
Section: Dmyc Is Repressed By Brat and Mei-p26 In Epithelial Cellsmentioning
confidence: 86%
“…The Drosophila strains used in this study are as follows: UASMei-P26 DNHL (kind gift from S. M. Cohen) (Li et al 2012); UASdMyc 42 (Johnston et al 1999); bantam sensor and control sensor (Brennecke et al 2003); UAS-brat RNAi and UAS-mei-P26 RNAi (ID nos. 105054 and 101060, Vienna Drosophila RNAi Center, Austria); and brat 192 , UAS-Brat, and UAS-Mei-P26 from the Bloomington Stock Center.…”
Section: Drosophila Strainsmentioning
confidence: 99%